2016
DOI: 10.1159/000445349
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Barrett's Oesophagus

Abstract: Background: Barrett's oesophagus (BO) is a premalignant condition associated with the development of oesophageal adenocarcinoma (OAC). Globally, the incidence of OAC is rising. Furthermore, the prognosis regarding the morbidity and mortality of OAC is bleak, with an estimated 5-year survival of 10-15%. Hence, detection of the premalignant phase is paramount. Endoscopy and biopsy sampling is the mainstay of diagnosis. Patients may present with symptoms of gastro-oesophageal reflux disease (GORD) or be completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…The duration of symptoms before endoscopy was significant for patients with EE but not for patients with BE. The study by Sharma N. et al ( 28 ) showed an increased risk of BE with in creasing duration of GERD symptoms. This may be explained by the fact that the majority of our patients had GERD for less than 5 years which may not be sufficient to cause Barrette mucosa (mean of duration of symptoms : 2.53 versus 2.84 years, p=0.74).…”
Section: Discussionmentioning
confidence: 99%
“…The duration of symptoms before endoscopy was significant for patients with EE but not for patients with BE. The study by Sharma N. et al ( 28 ) showed an increased risk of BE with in creasing duration of GERD symptoms. This may be explained by the fact that the majority of our patients had GERD for less than 5 years which may not be sufficient to cause Barrette mucosa (mean of duration of symptoms : 2.53 versus 2.84 years, p=0.74).…”
Section: Discussionmentioning
confidence: 99%
“…To examine the association with Barrett’s esophagus, we used binary logistic regression. All the regression models were adjusted for potentially confounding characteristics, including male sex, older age, higher BMI, lower LES resting pressures [ 19 - 23 ], positive H. pylori state [ 19 , 24 ], and abnormal multiple rapid swallows [ 25 ]. Data were cleaned and analyzed using the Python programming language version 3.8.6.…”
Section: Methodsmentioning
confidence: 99%
“…Barrett’s esophagus is also a complication with GERD following on from NERD and dysphagia, with some studies suggesting erosive esophagitis as a major risk factor for Barrett’s esophagus, with up to a fivefold increased risk [ 9 , 34 , 35 ]. The risk of Barrett’s esophagus increases with the length of time of untreated GERD [ 36 ] and is typically a precursor to esophageal adenocarcinoma [ 3 , 35 , 37 ]. Eusebi et al recently estimated the pooled prevalence of patients with confirmed Barrett’s esophagus in those with GERD at 7.0%, higher among those who drank alcohol [ 17 ].…”
Section: Reviewmentioning
confidence: 99%